PtBi / C catalyst for producing hydrogen by electrolyzing water as well as preparation method and application of PtBi / C catalyst
Preparation of PtBi/C catalyst by hydrothermal method solves the problems of uneven catalyst morphology and high loading of precious metals, and achieves efficient and stable water-electrical analytical hydrogen reaction, reducing costs and improving the durability of the catalyst.
Patent Information
- Application Number
- CN202411364124.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-28
AI Technical Summary
In the prior art, the nano-scale platinum group metal/transition metal alloy catalysts have uneven morphology, resulting in insufficient catalytic activity, high cost of precious metal loading, serious CO poisoning, affecting its application stability.
The PtBi catalyst is prepared by hydrothermal method and compounded with a carbon-based support to form a PtBi/C catalyst. The morphology and size of the catalyst are controlled through the specific ratio of platinum sources, metal reducing agents, surfactants and bismuth sources, and the use of precious metals is reduced. to improve catalytic activity.
It realizes efficient and stable water-electric hydrogen analytical reaction, reduces costs, improves the durability and hydrogen evolution performance of the catalyst, and is suitable for practical applications.
Smart Images

Figure CN119221018A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to a PtBi / C catalyst for producing hydrogen by electrolyzing water, and a preparation method and application thereof. Background Art
[0002] As a clean and efficient secondary energy source, hydrogen energy has attracted much attention among various forms of renewable energy, mainly because of its advantages of being eco-friendly, zero-emission, and having a high gravimetric calorific value of 120MJ / kg. Its combustion product is only water. Water electrolysis based on a mobile electrolyzer can also achieve a sustainable hydrogen economy.
[0003] Platinum-based electrocatalysts exhibit extraordinary intrinsic activity and stability for hydrogen evolution. However, the practical application of noble metal catalysts is limited by high cost and CO poisoning. However, as the noble metal loading decreases, the oxygen transfer resistance increases, and the limited accessible active sites lead to reduced durability.
[0004] To solve this problem, nanostructured electrocatalysts with a large surface-to-volume ratio and alloying of platinum group metals with transition metals can be sought. However, the nanoscale platinum group metal / transition metal alloys in the prior art are not uniform in morphology and size, and the formation of bulk products and differences in transition metal sources affect their catalytic activity. Therefore, the preparation of highly uniform nanoparticle platinum group metal / transition metal alloy catalysts with high electrocatalytic hydrogen evolution activity is a problem that those skilled in the art urgently need to solve. Summary of the invention
[0005] The purpose of the present invention is to provide a PtBi / C catalyst for producing hydrogen by electrolysis of water and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art. The catalyst for producing hydrogen by electrolysis of water provided by the present invention has a simple composition, uniform morphology, good stability, high catalytic efficiency, and lower cost than commercial hydrogen evolution catalysts.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] One of the technical solutions of the present invention: a method for preparing a PtBi / C catalyst for producing hydrogen by electrolysis of water, comprising the following steps:
[0008] Dispersing a platinum source, a metal reducing agent, a surfactant and a bismuth source in an organic solvent to obtain a mixed solution;
[0009] Performing a hydrothermal reaction on the mixed solution to obtain a PtBi catalyst;
[0010] Dispersing the PtBi catalyst and the carbon-based carrier in a solvent to obtain a mixed solution, and centrifugally washing the mixed solution to obtain a solid product;
[0011] The solid product is dispersed in an acid solution, heated and stirred, and then centrifugally washed and dried to obtain the PtBi / C catalyst.
[0012] Furthermore, the platinum source is one of acetylacetonate platinum, potassium tetrachloroplatinate, potassium chloroplatinate, sodium chloroplatinate and sodium tetrachloroplatinate; the metal reducing agent is one of molybdenum hexacarbonyl, tungsten hexacarbonyl and chromium hexacarbonyl; the surfactant is a cationic surfactant; the bismuth source is bismuth chloride or bismuth nitrate; the organic solvent is oleylamine; and the carbon-based carrier is one of conductive carbon black and carbon nanotubes.
[0013] Furthermore, the platinum source is preferably platinum acetylacetonate; the metal reducing agent is preferably molybdenum hexacarbonyl; the bismuth source is preferably bismuth chloride; and the carbon-based carrier is preferably conductive carbon black.
[0014] Furthermore, the cationic surfactant is cetyltrimethylammonium bromide (CTAB).
[0015] Furthermore, the platinum ion concentration of the platinum source in the mixed solution is 0.005 mmol / mL, the bismuth ion concentration of the bismuth source is 0.0003-0.0025 mmol / mL, the concentration of the metal reducing agent is 0.0076 mmol / mL, and the concentration of the surfactant is 0.055 mmol / mL; the temperature of the hydrothermal reaction is 200° C., and the time is 0.5-5 h.
[0016] Furthermore, the molar ratio of platinum ions to bismuth ions in the mixed solution is 1:0.06-0.5, preferably 1:0.5.
[0017] Furthermore, the hydrothermal reaction time is preferably 5 h.
[0018] When the reaction time is too low, the uniformity of the morphology and catalytic activity of the prepared PtBi catalyst will be affected.
[0019] Furthermore, the carbon-based carrier is conductive carbon black; the solvent is cyclohexane; and the acid solution is 36 wt % acetic acid.
[0020] Furthermore, the mass ratio of the PtBi catalyst to the carbon-based carrier is 1:2.
[0021] Furthermore, the dosage ratio of the solid product to the acid solution is 1 mg:1 mL.
[0022] Furthermore, after the hydrothermal reaction is completed, a centrifugal washing operation is also included.
[0023] Furthermore, the heating and stirring is carried out at a temperature of 70° C. for no less than 12 hours; and the centrifugal washing is carried out using a mixed solution of cyclohexane and ethanol.
[0024] Furthermore, the centrifugal washing after the hydrothermal reaction is specifically performed by centrifugal washing using a mixed solution of cyclohexane and ethanol in a volume ratio of 1:6;
[0025] The centrifugal washing of the mixed solution to obtain the solid product specifically comprises centrifugal washing with a mixed solution of cyclohexane and ethanol in a volume ratio of 6:1;
[0026] The solid product is dispersed in an acid solution, heated and stirred, and then centrifugally washed and dried to obtain the PtBi / C catalyst. The centrifugal washing is specifically centrifugally washed using a mixed solution of cyclohexane and ethanol in a volume ratio of 6:1.
[0027] The second technical solution of the present invention: a PtBi / C catalyst for producing hydrogen by electrolysis of water, prepared by the above preparation method.
[0028] Furthermore, the PtBi / C catalyst includes a carbon-based carrier and a PtBi alloy supported on the carbon-based carrier, wherein the molar ratio of Pt to Bi is 1:0.008-0.114.
[0029] The third technical solution of the present invention: an application of the above-mentioned PtBi / C catalyst in catalytic hydrogen production by water electrolysis under alkaline conditions.
[0030] Technical solution four of the present invention: an electrode for producing hydrogen by electrolyzing water, wherein the active component of the electrode includes the above-mentioned PtBi / C catalyst.
[0031] The fifth technical solution of the present invention: an application of the above-mentioned electrode for producing hydrogen by electrolysis of water in alkaline water electrocatalytic hydrogen production.
[0032] Furthermore, the application method is: at 25°C and normal pressure, using potassium hydroxide as the electrolyte, Hg / HgO as the reference electrode, a carbon rod as the counter electrode, and the electrode for electrolyzing water to produce hydrogen as the working electrode, electrolyzing water to produce hydrogen in a potassium hydroxide alkaline solution.
[0033] The present invention discloses the following technical effects:
[0034] The present invention adopts a one-pot hydrothermal method to prepare a PtBi catalyst, and then composites it with a carbon-based carrier to prepare a PtBi / C catalyst. The process is simple, and it is easy to prepare in large quantities, and the morphology and size of the catalyst can be effectively controlled.
[0035] The catalyst of the present invention is obtained by loading a specific proportion of PtBi alloy on a carbon-based carrier. After the catalyst is prepared as a working electrode, an efficient water electrolysis hydrogen reaction can be achieved at a relatively low overpotential, and the catalyst has relatively excellent stability. The cost of the water electrolysis hydrogen production reaction is reduced and its hydrogen evolution performance is improved by doping with transition metals, which is beneficial to practical applications.
[0036] The catalyst of the present invention has low production cost and simple preparation method. The method of transition metal doping and active component attachment to carbon-based carrier can effectively reduce the usage of Pt and ensure that the catalyst has excellent ability of hydrogen evolution by electrolysis of water. The catalyst has significant long-term stability and its activity decay is almost negligible after continuous operation for 30 hours. The catalyst has broad application prospects in efficient hydrogen production by electrolysis of water. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 HAADF-STEM, HRTEM and STEM-EDS elemental mapping diagrams of the PtBi / C catalyst prepared in Example 8, wherein (a) is a HAADF-STEM diagram, (b) to (c) are HRTEM diagrams, and (d) to (f) are STEM-EDS elemental analysis diagrams;
[0039] Figure 2 is the XRD pattern of the PtBi / C catalysts prepared in Examples 5 to 8;
[0040] Figure 3 The linear voltammetry diagram of the hydrogen evolution reaction of the working electrode prepared from the catalysts of Examples 1 to 8 and Comparative Example 1 and the linear voltammetry diagram of the hydrogen evolution reaction at -10 mA cm -2 、-100mA cm -2 The corresponding overpotential under current density, where (a) to (b) are linear voltammetry diagrams and (c) is the overpotential diagram;
[0041] Figure 4 The impedance spectra of the working electrodes prepared from the catalysts of Examples 1 to 8 and Comparative Example 1;
[0042] Figure 5 The long-term multi-current stability test results of the working electrode prepared from the catalyst of Example 8;
[0043] Figure 6 TEM images of PtBi / C catalysts prepared at different hydrothermal reaction times in Examples 8 to 11, wherein (a) is Example 9, (b) is Example 10, (c) is Example 11, and (d) is Example 8;
[0044] Figure 7The hydrogen evolution performance test results of the working electrodes prepared from the catalysts of Examples 8 to 11;
[0045] Figure 8 The results of the hydrogen evolution performance test of the working electrodes prepared using the catalysts of Example 8 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0046] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0047] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0048] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0049] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0050] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0051] The raw materials and reagents used in the present invention are all commercially available products.
[0052] Example 1
[0053] A PtBi / C catalyst for producing hydrogen by electrolysis of water, the preparation steps of which are as follows:
[0054] 20 mg (0.05 mmol) of platinum acetylacetonate, 20 mg (0.076 mmol) of molybdenum hexacarbonyl, 200 mg (0.55 mmol) of CTAB, and 1 mg (0.003 mmol) of bismuth nitrate were dissolved in a 100 mL flask containing 10 mL of oleylamine and ultrasonically dispersed for 30 min to obtain a mixed solution; the obtained mixed solution was subjected to a hydrothermal reaction at 200° C. in an oil bath for 5 h, and after the reaction, it was centrifuged and washed with a mixed solution of cyclohexane and ethanol (volume ratio 1:6) to obtain a PtBi catalyst (5 mg); 10 mg of conductive carbon black and 30 mL of cyclohexane were added to a beaker containing the above PtBi catalyst at a mass ratio of 1:2 to the conductive carbon black, and then ultrasonically dispersed, and the obtained mixed solution was centrifuged and washed with a mixed solution of cyclohexane and ethanol (volume ratio 6:1), and the washed solid product was transferred to a beaker containing 15 mL of acetic acid at a ratio of 1 mg:1 mL to the solid product. The catalyst was prepared by centrifugation and washing with a mixed solution of cyclohexane and ethanol (volume ratio 6:1), and then dried to obtain a PtBi / C catalyst. The composition of the PtBi / C catalyst was PtBi 0.008 / C.
[0055] Example 2
[0056] Compared with Example 1, the only difference is that the amount of bismuth nitrate added is 2 mg (0.006 mmol), the amount of conductive carbon black added is changed according to the amount of PtBi catalyst generated, and the amount of acetic acid used is changed according to the amount of solid product. After XPS testing, the product is recorded as PtBi 0.02 / C.
[0057] Example 3
[0058] Compared with Example 1, the only difference is that the amount of bismuth nitrate added is 4 mg (0.012 mmol), the amount of conductive carbon black added is changed according to the amount of PtBi catalyst generated, and the amount of acetic acid is changed according to the amount of solid product. After XPS testing, the product is recorded as PtBi 0.044 / C.
[0059] Example 4
[0060] Compared with Example 1, the only difference is that the amount of bismuth nitrate added is 8 mg (0.024 mmol), the amount of conductive carbon black added is changed according to the amount of PtBi catalyst generated, and the amount of acetic acid is changed according to the amount of solid product. After XPS testing, the product is recorded as PtBi 0.091 / C.
[0061] Example 5
[0062] Compared with Example 1, the only difference is that the bismuth source is bismuth chloride (0.003 mmol). After XPS testing, the product is recorded as PtBi 0.011 / C.
[0063] Example 6
[0064] Compared with Example 5, the only difference is that the amount of bismuth chloride added is 2 mg (0.006 mmol), the amount of conductive carbon black added is changed according to the amount of PtBi catalyst generated, and the amount of acetic acid used is changed according to the amount of solid product. After XPS testing, the product is recorded as PtBi 0.026 / C.
[0065] Example 7
[0066] Compared with Example 5, the only difference is that the amount of bismuth chloride added is 4 mg (0.012 mmol), the amount of conductive carbon black added is changed according to the amount of PtBi catalyst generated, and the amount of acetic acid is changed according to the amount of solid product. After XPS testing, the product is recorded as PtBi 0.055 / C.
[0067] Example 8
[0068] Compared with Example 5, the only difference is that the amount of bismuth chloride added is 8 mg (0.024 mmol), the amount of conductive carbon black added is changed according to the amount of PtBi catalyst generated, and the amount of acetic acid is changed according to the amount of solid product. After XPS testing, the product is recorded as PtBi 0.114 / C.
[0069] Example 9
[0070] Compared with Example 8, the only difference is that the mixed solution is subjected to hydrothermal reaction at 200° C. in an oil bath for 0.5 h, and the product is recorded as PtBi / C-0.5.
[0071] Example 10
[0072] Compared with Example 9, the only difference is that the mixed solution is subjected to hydrothermal reaction at 200° C. in an oil bath for 1 h, and the product is recorded as PtBi / C-1.
[0073] Embodiment 11
[0074] Compared with Example 9, the only difference is that the mixed solution is subjected to hydrothermal reaction at 200° C. for 2 h in an oil bath, and the product is recorded as PtBi / C-2.
[0075] Comparative Example 1
[0076] The commercially available Pt / C catalyst is provided by Suzhou Yilongsheng Energy Technology Co., Ltd., with specifications of 20wt% platinum-carbon catalyst.
[0077] Comparative Example 2
[0078] Compared with Example 8, the only difference is that the mixed solution is subjected to hydrothermal reaction at 140° C. in an oil bath for 5 h, and the product is recorded as PtBi / C-140.
[0079] Test Case
[0080] (1) Characterization of catalyst morphology, structure and composition
[0081] The morphology and composition of the PtBi / C catalyst prepared in Example 8 were characterized by high-angle annular dark field scanning TEM (HAADF-STEM), high-resolution transmission electron microscopy (HRTEM) and STEM-EDS elemental mapping. Figure 1 shown.
[0082] Figure 1 The HAADF-STEM, HRTEM and STEM-EDS elemental mapping diagrams of the PtBi / C catalyst prepared in Example 8, where (a) is the HAADF-STEM diagram, (b) to (c) are HRTEM diagrams, and (d) to (f) are STEM-EDS elemental analysis diagrams. As can be seen from (a), the catalyst prepared in Example 8 is mainly round particles with highly uniform morphology and an average diameter of about 5nm. From (b) to (c), clear lattice fringes with spacings of 0.232nm and 0.203nm can be observed, pointing to the intermetallic compound PtBi (111) and (200) crystal planes (inset in (b)), respectively. This result is consistent with Figure 2 The XRD results in (d) to (f) correspond to the coexistence of Pt and Bi elements and their uniform distribution in the entire particle, further confirming the intermetallic structure. The catalysts prepared in Examples 1 to 7 have a particle size of 4-5 nm in diameter.
[0083] The PtBi / C catalysts prepared in Examples 5 to 8 were characterized by X-ray diffractometer (XRD). Figure 2 As shown in the figure, PtBi 0.011 / C、PtBi 0.026 / C、PtBi 0.055 / C、PtBi 0.114 / C correspond to Examples 5 to 8, respectively. The straight lines refer to the peak positions of the standard Pt (red) and Bi (light blue) samples. It can be clearly seen that the PtBi / C catalysts prepared in Examples 5 to 8 basically match the standard characteristic peaks of Pt (JCPDS 04-0802), but no characteristic peaks corresponding to Bi (JCPDS 85-1329) appear, indicating that the content of Bi element is relatively low. As the amount of Bi input increases, the characteristic peaks corresponding to Pt gradually shift to higher angles. The main diffraction peaks of the PtBi / C catalyst prepared in Example 8 appear at 40.2°, 46.76° and 67.84°, which are attributed to the (111), (200) and (220) planes of Pt, respectively, while the peak positions of the standard Pt (111) are located at 39.76°, 46.24° and 67.45°, respectively. This phenomenon well indicates the formation of the intermetallic structure and the compression of the Pt lattice.
[0084] (2) Electrochemical performance test
[0085] 2 mg of catalyst (the PtBi / C catalysts finally prepared in Examples 1 to 11 and the catalyst in Comparative Example 1 are used as the catalyst to be tested) is weighed and added to a mixed solution of 600 μL of isopropanol, 390 μL of deionized water and 10 μL of 5% Nafion solution to prepare a mixed suspension. After ultrasonic treatment, 10 μL of the mixed suspension is dropped onto a glassy carbon electrode and naturally dried to obtain a working electrode.
[0086] The relevant parameters of the three-electrode system for hydrogen evolution reaction performance test are as follows:
[0087] Working electrode: glassy carbon electrode (glassy carbon electrode diameter: 5mm, area: 0.196cm 2 , load the corresponding catalyst for testing);
[0088] Reference electrode: Hg / HgO electrode;
[0089] Counter electrode: graphite rod electrode;
[0090] Electrolyte: 1M KOH.
[0091] In 1M KOH solution, the voltage range of -0.475 to 0.074 V vs. RHE was used to perform a reverse LSV test at a scan rate of 20 mV / s to evaluate the hydrogen evolution performance and corresponding overpotential comparison of the working electrodes prepared by the catalysts of Examples 1 to 8 and Comparative Example 1. The results are shown in FIG. Figure 3 shown.
[0092] Figure 3 The linear voltammetry diagram of the hydrogen evolution reaction of the working electrode prepared from the catalysts of Examples 1 to 8 and Comparative Example 1 and the linear voltammetry diagram of the hydrogen evolution reaction at -10 mA cm -2 、-100mAcm-2 The overpotential corresponding to the current density, where (a) to (b) are linear voltammetry diagrams and (c) is the overpotential diagram. Figure 3 It can be seen that in the 1M KOH solution hydrogen evolution performance test, the hydrogen evolution performance of the working electrodes prepared by the catalysts prepared in Examples 1 to 8 of the present invention is mostly better than that of the Pt / C catalyst in Comparative Example 1 (-10 mA cm -2 、-100mAcm -2 The corresponding overpotentials are 49mV and 268mV respectively). Among them, Example 1 is at -10mAcm -2 、-100mA cm -2 The corresponding overpotentials are 32mV and 169mV, 42mV and 218mV in Example 2, 44mV and 281mV in Example 3, 54mV and 373mV in Example 4, 40mV and 235mV in Example 5, 54mV and 349mV in Example 6, 47mV and 272mV in Example 7, and 36mV and 226mV in Example 8. It can be seen that the addition of different bismuth sources shows different trends in hydrogen evolution catalytic activity. In Examples 1 to 4 with bismuth nitrate as the bismuth source, the trend of hydrogen evolution catalytic activity is first good and then bad. The catalyst prepared in Example 1 with a relatively high content of Pt addition has the best hydrogen evolution catalytic activity and has the best hydrogen evolution performance in Examples 1 to 8. In Examples 5 to 8 with bismuth chloride as the bismuth source, the trend of hydrogen evolution catalytic activity shows a "volcano type", and the catalyst prepared in Example 8 with the smallest relative content of Pt addition has the best hydrogen evolution catalytic activity. Since Example 8 has the highest Bi content, the proportion of precious metal Pt is relatively reduced, taking both cost and efficient hydrogen evolution catalytic activity into account, so Example 8 can be the most preferred PtBi / C catalyst.
[0093] Electrochemical impedance spectroscopy (EIS) was used to study the charge transfer kinetics of the working electrodes prepared from the catalysts of Examples 1 to 8 and Comparative Example 1 during the hydrogen evolution reaction. Figure 4 shown.
[0094] Figure 4 The impedance spectra of the working electrodes prepared from the catalysts of Examples 1 to 8 and Comparative Example 1 are shown in FIG. Figure 4 It can be seen that the PtBi / C series materials of Examples 1 to 8 all exhibit smaller charge transfer resistance than the Pt / C of Comparative Example 1, and the smallest charge transfer resistance is observed in the catalyst prepared in Example 8.
[0095] The electrochemical stability was evaluated by recording the VT curve under constant current. The catalyst prepared in the most preferred embodiment 8 was used as the target catalyst to prepare the working electrode, and a long-term multi-current stability test was performed. The multi-current was tested using a six-stage (constant current -10 mA cm -2、-30mAcm -2 、-50mA cm -2 、-80mA cm -2 、-100mA cm -2 、-10mAcm -2 ) Each section was tested for 5 hours of stability. The results were as follows: Figure 5 shown.
[0096] Figure 5 The long-term multi-current stability test results of the working electrode prepared by the catalyst of Example 8. Figure 5 It can be seen that the stability is excellent within the 30h test period. After 25h of testing, the constant current is -10mAcm -2 , 5h test, the voltage corresponding to the 30th hour (85mV) is almost the same as that of the 5th hour (87mV), indicating that it has good durability.
[0097] (3) Effect of hydrothermal reaction time on catalyst morphology and performance
[0098] Figure 6 TEM images of PtBi / C catalysts prepared under different hydrothermal reaction times in Examples 8 to 11, wherein (a) is Example 9, (b) is Example 10, (c) is Example 11, and (d) is Example 8. Figure 6 It can be seen that in (a), there are small particles with a diameter of about 4-7nm and larger block products with an aspect ratio (60nm:30nm) of about 2. In (b) to (d), as the reaction time increases, the block products gradually decrease, generating products with 4-6nm particles as shown in Figures (b) and (c). Finally, when the reaction time is increased to 5h, the product exists in the form of a large number of small round particles with an average diameter of about 5nm.
[0099] Figure 7 The hydrogen evolution performance test diagram of the working electrode prepared by the catalysts of Examples 8 to 11 is shown in FIG. Figure 7 It can be seen that with the increase of reaction time, the hydrogen evolution performance of the corresponding catalyst is significantly improved, which is related to the morphology and size of the catalyst.
[0100] Figure 8 The results of the hydrogen evolution performance test of the working electrode prepared by the catalysts of Example 8 and Comparative Example 2 are shown in FIG. Figure 8 It can be concluded that comparative example 2 is -10mAcm -2 、-100mAcm -2 The corresponding overpotentials are 75 mV and 422 mV, respectively, which are significantly inferior to the catalyst of Example 8. Therefore, the hydrothermal reaction temperature is preferably 200°C.
[0101] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a PtBi / C catalyst for producing hydrogen by electrolysis of water, characterized in that: The following steps are involved: Dispersing a platinum source, a metal reducing agent, a surfactant and a bismuth source in an organic solvent to obtain a mixed solution; Performing a hydrothermal reaction on the mixed solution to obtain a PtBi catalyst; Dispersing the PtBi catalyst and the carbon-based carrier in a solvent to obtain a mixed solution, and centrifugally washing the mixed solution to obtain a solid product; The solid product is dispersed in an acid solution, heated and stirred, and then centrifugally washed and dried to obtain the PtBi / C catalyst.
2. The method for preparing a PtBi / C catalyst for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The platinum source is one of acetylacetonate platinum, potassium tetrachloroplatinate, potassium chloroplatinate, sodium chloroplatinate and sodium tetrachloroplatinate; the metal reducing agent is one of molybdenum hexacarbonyl, tungsten hexacarbonyl and chromium hexacarbonyl; the surfactant is a cationic surfactant; the bismuth source is bismuth chloride or bismuth nitrate; the organic solvent is oleylamine; and the carbon-based carrier is one of conductive carbon black and carbon nanotubes.
3. The method for preparing a PtBi / C catalyst for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The solvent is cyclohexane; the acid solution is 36 wt % acetic acid.
4. The method for preparing a PtBi / C catalyst for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The platinum ion concentration of the platinum source in the mixed solution is 0.005 mmol / mL, the bismuth ion concentration of the bismuth source is 0.0003-0.0025 mmol / mL, the concentration of the metal reducing agent is 0.0076 mmol / mL, and the concentration of the surfactant is 0.055 mmol / mL; the temperature of the hydrothermal reaction is 200° C., and the time is 0.5-5 h.
5. The method for preparing a PtBi / C catalyst for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The mass ratio of the PtBi catalyst to the carbon-based carrier is 1:
2.
6. The method for preparing a PtBi / C catalyst for producing hydrogen by electrolysis of water according to claim 1, characterized in that: The heating and stirring temperature is 70° C. and the time is not less than 12 hours; the centrifugal washing is performed by centrifugal washing using a mixed solution of cyclohexane and ethanol.
7. A PtBi / C catalyst for producing hydrogen by electrolysis of water, obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the PtBi / C catalyst as claimed in claim 7 in catalytic hydrogen production by water electrolysis under alkaline conditions.
9. An electrode for producing hydrogen by electrolysis of water, characterized in that: The active component of the electrode includes the PtBi / C catalyst according to claim 7.
10. Use of the electrode for producing hydrogen by electrolysis of water as claimed in claim 9 in alkaline water electrocatalytic hydrogen production.
Citation Information
Patent Citations
Preparation method of highly-active platinum-bismuth alloy fuel cell anode catalyst
CN108598496A
Preparation method and application of rubber shell-shaped PtBi electrocatalyst
CN115472853A
Intermetallic compound catalyst with high catalytic activity as well as preparation method and application thereof
CN118147701A